Strengthening Local Product Identity Through Trademark Protection in Sendang Mulya Sari Village, Konawe Regency - Rahman Hasima; St. Muslimah Suciati; Mutia Nur Fadhilah Ruslan (Universitas Negeri Gorontalo, 2026)
This article sought to nurture legal consciousness and deepen the understanding of local entrepreneurs in Sendang Mulya Sari Village of trademark protection as a fundamental legal instrument for safeguarding the identity and dignity of local products. The activity was carried out in three deliberate phases: preparation, encompassing field surveys, meaningful engagement with village authorities, and a thorough examination of the community's legal vulnerabilities; implementation, opened with a pretest to capture participants' initial grasp of trademark law; and evaluation, in which a posttest was administered to reflect upon the legal knowledge internalized following material delivery. The activity drew upon face-to-face lectures and dialogic discussions, guided by an approach that was persuasive, educational, communicative, and deeply attentive to the socio-legal realities of the community. The findings bore witness to a meaningful shift in participants' legal consciousness. Prior to the intervention, 80% of participants (n=32) demonstrated very low comprehension of trademark law as a protective legal framework. Following the intervention, 60% (n=24) attained a high level of legal understanding and 20% (n=8) reached a very high level, with no participants remaining at a low comprehension level a testament to the transformative role of community-based legal education in bridging the gap between law in the books and law in action.